Long-term depression is differentially expressed in distinct lamina of hippocampal CA1 dendrites - Ramachandran, Binu; Ahmed, Saheeb; Dean, Camin (Frontiers in Cellular Neuroscience, 2015)
Information storage in CA1 hippocampal pyramidal neurons is compartmentalized in proximal versus distal apical dendrites, cell bodies, and basal dendrites. This compartmentalization is thought to be essential for synaptic integration. Differences in the expression of LTP in each of these compartments have been described, but less is known regarding potential differences in LTD. Here, to directly compare LTD expression in each compartment and to bypass possible differences in input-specificity and stimulation of presynaptic inputs, we used global application of NMDA to induce LTD. We then examined LTD expression in each dendritic sub-region - proximal and distal apical, and basal dendrites - and in cell bodies. Interestingly, we found that distal apical dendrites exhibited the greatest magnitude of LTD of all areas tested and this LTD was maintained, whereas LTD in proximal apical dendrites was not maintained. In basal dendrites, LTD was also maintained, but the magnitude of LTD was less than in distal apical dendrites. Blockade of inhibition blocked LTD maintenance in both distal apical and basal dendrites. Population spikes recorded from the cell body layer correlated with apical dendrite fEPSPs, where LTD was maintained in distal dendrites and decayed in proximal dendrites. On the other hand, LTD of basal dendrite fEPSPs was maintained but population spike responses were not. Thus E-S coupling was distinct in basal and apical dendrites. Our data demonstrate cell autonomous differential information processing in somas and dendritic sub-regions of CA1 pyramidal neurons in the hippocampus, where LTD expression is intrinsic to distinct dendritic regions, and does not depend on the nature of stimulation and input specificity.